THE ANALYSIS OF SERVICE QUALITY IMPACT ON CUSTOMERS’ SATISFACTION (Case Study of “Mas Alief” Automotive Workshop Bangkalan.) - Sandra Oktaviana Pinaraswati; Ilya Farida; Sri Susilowati; Suprihati Suprihati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the impact of service quality of